Проектно- исследовательская деятельность в начальных классах – как средство формирования умения самостоятельно добывать знания - Боженко, О. Г. (My University, 2016)
In this article it is observed the project's method as one of the good modern teaching methods, its practical usage on lessons and extracurricular work. Author analyses working experience and comes to conclusion that projecting - researching activity lets pupils to wide up knowledge of environment and to use practical experience. Given article would be interesting for students of pedagogical universities and for practicing teachers as well.
Keywords: the project activity; project; primary school